2013
DOI: 10.1155/2013/519627
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Inflammation in the CNS during Chronic EAE Despite Local Absence of IL-17 Production

Abstract: Experimental autoimmune encephalomyelitis (EAE) is an artificially induced demyelination of the central nervous system (CNS) that resembles multiple sclerosis in its clinical, histopathological, and immunological features. Activated Th1 and Th17 cells are thought to be the main immunological players during EAE development. This study was designed to evaluate peripheral and local contribution of IL-17 to acute and chronic EAE stages. C57BL/6 mice were immunized with MOG plus complete Freund's adjuvant followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 49 publications
6
26
1
Order By: Relevance
“…The effects of infiltrating cells on the CNS during the course of EAE depend on the release of cytokines and chemokines that are responsible for neuroinflammation [31]. In order to determine the inflammatory We found significant differences between CFA and EAE groups in IFN, TNF, IL-10 and IL-1 mRNA expression levels (Fig.…”
Section: Mecp2 308/y Mice Show Higher and Persisting Inflammatory Resmentioning
confidence: 95%
See 1 more Smart Citation
“…The effects of infiltrating cells on the CNS during the course of EAE depend on the release of cytokines and chemokines that are responsible for neuroinflammation [31]. In order to determine the inflammatory We found significant differences between CFA and EAE groups in IFN, TNF, IL-10 and IL-1 mRNA expression levels (Fig.…”
Section: Mecp2 308/y Mice Show Higher and Persisting Inflammatory Resmentioning
confidence: 95%
“…Myeloid cells are key for the onset and progression of EAE. These cells adopt different phenotypes that coexist in the CNS after MOG immunization, and the balance between these phenotypes and the immune mediators they release are essential for mantainance of the chronic phase [31]. Since it has been shown that MeCP2 is expressed in microglial cells and that its deletion can alter the lifespan and pathogenic phenotype in mice [32], we sought to evaluate the level of microgliosis after EAE-induction.…”
Section: Mecp2 Deficit Does Not Alter the Expression Of Iba1 And Micrmentioning
confidence: 99%
“…EAE was induced as previously reported [37]. Briefly, mice were immunized with 150  μ g of MOG 35–55 emulsified in CFA containing 400  μ g of BCG.…”
Section: Methodsmentioning
confidence: 99%
“…Animals that survive EAE recover in the period between the 30th and 40th days after the sensitization. Resensitization can induce the disease again with previously actively induced EAE, only by a passive transmission of the myelin antigen (Zorzella-Pezavento et al, 2013).…”
Section: Experimental Autoimmune Encephalomyelitis (Eae)mentioning
confidence: 99%